2023
DOI: 10.1101/gr.277792.123
|View full text |Cite
|
Sign up to set email alerts
|

The human genome contains over a million autonomous exons

Nicholas Stepankiw,
Ally W.H. Yang,
Timothy R. Hughes

Abstract: Mammalian mRNA and lncRNA exons are often small compared to introns. The exon definition model predicts that exons splice autonomously, dependent on proximal exon sequence features, explaining their delineation within large introns. This model has not been examined on a genome-wide scale, however, leaving open the question of how often mRNA and lncRNA exons are autonomous. It is also unknown how frequently such exons can arise by chance. Here, we directly assayed large fragments (500–1000 bp) of the human geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Nevertheless, certain important characteristics have been identified that are common to a majority of lncRNAs. For instance, over 81% of lncRNAs are poorly conserved and contain fewer exons relative to mRNAs [ 24 , 102 ] due to less efficient and chaotic splicing relative to mRNAs [ 103 ].…”
Section: Biological Characteristics Of Lncrnasmentioning
confidence: 99%
“…Nevertheless, certain important characteristics have been identified that are common to a majority of lncRNAs. For instance, over 81% of lncRNAs are poorly conserved and contain fewer exons relative to mRNAs [ 24 , 102 ] due to less efficient and chaotic splicing relative to mRNAs [ 103 ].…”
Section: Biological Characteristics Of Lncrnasmentioning
confidence: 99%